Invisibilidade social a partir do filme “O som ao redor”: uma análise honnethiana das patologias sociais no Brasil - Thiago Aguiar Simim (Ciências Sociais Unisinos)
This paper discusses the convergence between literature and social-political analysis in Axel Honneth’s social philosophy, more precisely in his most recent work. Honneth demonstrates how primarily films and novels can draw attention to social pathologies in the sense pursued in his model of critical theory, thus creating tracks to investigate a particular understanding of a society situated in its time. Thus, this paper starts by focusing on the delineation of what is meant by social pathology and some of its modes in Honneth’s theory of recognition. It then analyzes how Honneth draws on works of art to identify social pathologies and subsequently applies this method of analysis to the Brazilian film “Neighboring sounds”, of director Kleber Mendonça Filho. In the conclusion it returns to the consideration of the mechanism of social pathologies that cause invisibility as impediments to social emancipation and how these barriers can be analyzed from a methodological point of view in consonance with the critical theory.